Understanding Tax Engagement Challenges among Unstructured MSMEs: A Contextual Behavioral Perspective from Bali’s Tourism Economy - Alifia Ainun Nisa; Agustin Fadjarenie; Ronny Andesto; Deden Tarmidi; Dyah Rizkyan Dewi (Jurnal Perpajakan dan Keuangan Publik, 2026)
This study examines how unstructured MSMEs in Bali’s tourism areas perceive digital tax administration and how behavioral, cultural, and institutional factors influence their tax engagement. Using an interpretive qualitative approach, we conducted semi-structured interviews with 12 participants, including MSME operators, tax officials, academic experts, and a cultural informant. Data were analyzed using reflexive thematic analysis. The findings reveal five key themes: limited understanding of digital taxation despite the adoption of digital payments; differences in digital and tax engagement among participants; the importance of community values and traditional institutions; limited tax socialization; and low awareness of tax-related risks. The study identifies compliance distance as a condition where potential taxpayers have limited connection with formal tax systems, rather than as deliberate non-compliance. It proposes the Value-Based Tax Governance Compliance Model as a contextual extension of existing tax compliance perspectives by incorporating community values and informal governance institutions. The Contextual Behavioral Compliance Framework (CBCF) is presented as a policy-oriented framework requiring further empirical testing for inclusive digital tax strategies.